2023
DOI: 10.1007/s12325-023-02473-6
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological, Clinical, Patient-Reported and Economic Burden of Inflammatory Bowel Disease (Ulcerative colitis and Crohn’s disease) in Spain: A Systematic Review

Abstract: Introduction This study describes the epidemiological, clinical, patient-reported and economic burden of inflammatory bowel disease (IBD), including Crohn’s disease (CD) and ulcerative colitis (UC), in Spain. Methods A systematic review was performed of observational studies reporting the epidemiological, clinical, patient-reported and economic burden of IBD in the Spanish population, from 2011 to 2021. Original articles and conference abstracts published in English or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 69 publications
2
7
0
Order By: Relevance
“…Similarly, an American study 37 also showed a higher incidence of UC than CD. Our findings also showed a higher prevalence of anxiety‐depression and poorer QoL in patients with UC compared with CD, which is consistent with the trend of some studies, 38,39 but inconsistent with the results of many studies in other countries 40–44 . In the studies by Caplan et al 39 .…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…Similarly, an American study 37 also showed a higher incidence of UC than CD. Our findings also showed a higher prevalence of anxiety‐depression and poorer QoL in patients with UC compared with CD, which is consistent with the trend of some studies, 38,39 but inconsistent with the results of many studies in other countries 40–44 . In the studies by Caplan et al 39 .…”
Section: Discussionsupporting
confidence: 60%
“…and Ganguli et al., 38 the results obtained showed a higher QoL in the group of patients with CD, although none of these studies showed statistically significant differences between groups. However, among Western countries, a UK study 40 showed a higher prevalence of anxiety‐depression in CD than in UC, and a systematic review in Spain 41 showed a higher prevalence of anxiety‐depression in CD than in UC among adults. A study from Korea, 41 despite being an Asian country, showed a higher prevalence of anxiety‐depression in CD than in UC, although there was no statistical difference.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, epidemiological studies have confirmed that there are significant gender differences in the incidence of IBD, and this difference shows significant regional differences. In the USA,45 Canada,46 47 Israel,28 Spain48 and Denmark,49 the incidence of women is higher than that of men. In Asian countries such as South Korea,50 India51 and China,52 the incidence is higher in men than in women.…”
Section: Discussionmentioning
confidence: 99%